The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/4582838
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cross‐Border e‐Commerce Logistics Supervision System Based on Internet of Things Technology

Abstract: Based on the Internet of Things technology, this paper proposes building a cross-border e-commerce logistics supervision system and determines the evaluation index system from the overall framework design of the system, supply chain supervision process optimization, risk supervision optimization, and system order degree optimization. First of all, the framework adopts the national certification center to supervise the logistics service platform and logistics service platform to supervise the logistics particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The intelligent supervision system for supply chain finance and logistics operation is built on the basis of Internet of Things to collect, process, and exchange information and support system activities such as the transmission of information on the production and circulation of goods [ 32 35 ]. The platform consists of application layer, data integration and interaction layer, and perception operation layer, as shown in the structure diagram of Figure 3 .…”
Section: An Intelligent Supervision System For Scm and Logisticsmentioning
confidence: 99%
“…The intelligent supervision system for supply chain finance and logistics operation is built on the basis of Internet of Things to collect, process, and exchange information and support system activities such as the transmission of information on the production and circulation of goods [ 32 35 ]. The platform consists of application layer, data integration and interaction layer, and perception operation layer, as shown in the structure diagram of Figure 3 .…”
Section: An Intelligent Supervision System For Scm and Logisticsmentioning
confidence: 99%
“…Jiang and other scholars summarized and analyzed according to the operation law of the logistics platform and found that there is a problem of low intelligence in the influencing factors of e-commerce platforms on logistics management [ 6 ]. Sun and other scholars improved the discrete representation method of e-commerce platforms in the operation process according to the different characteristics and types of logistics information in different regions [ 7 ]. Dong and other scholars conducted differentiation analysis according to the process of logistics management of the e-commerce platform and realized the specific representation of the logistics management characteristics of the e-commerce platform according to the fixed key information [ 8 ].…”
Section: Related Workmentioning
confidence: 99%
“…For the flow of cross-border data, China can set a regulatory threshold. For the normal cross-border flow of data, there are no obstacles, but only the cross-border flow of data reaches the corresponding threshold [27].…”
Section: Vigorously Improve the Laws And Regulations On The Protectio...mentioning
confidence: 99%